What can reunification of East and West Germany tell us about the cause of the allergy epidemic?. Issue 1 (January 2015) - Krämer, U.; Schmitz, R.; Ring, J.; Behrendt, H.
Summary The increase of allergies in East Germany – reaching West German prevalence shortly after the reunification – is considered a model for the allergy epidemic in the western world. Whether such a pattern was observed in all comparison studies and for all allergic manifestations is not known because a complete overview is missing. Hints about possible causal factors for the allergy epidemic could be gained by identifying known risk factors, which explain the observed pattern of allergy development in Germany. Again, an overview about these efforts is missing. We identified 14 cross‐sectional studies conducted after 1989 and calculated prevalence ratios (West/East) for asthma, hayfever, eczema and allergic sensitization. Additionally, a tabular overview about the explanatory power of risk factors hypothesized in the nineties and covering outdoor exposure, indoor factors, early childhood influences, nutrition as well as awareness is given. At the time of the German reunification, the prevalence ratio West/East was largest for hayfever and sensitization to birch pollen, less pronounced for the other phenotypes and even less than one for atopic eczema. Hayfever and sensitization to birch pollen also showed the steepest increase in East Germany afterwards. Single‐room heating with fossil fuels and living as only child in a family were identified as explaining up to 23.5% of the excess trend in East compared to the trend in West. Hayfever as most typical atopic disease showed the difference in allergy pattern between East and West Germany clearest. Risk factors identified for these phenotypes are completely different (single child) or even act in the opposite direction (single‐room heating) from classical risk factors for airway diseases. This might be the most important lesson from the West/East German experience. It already stimulated many other studies focussing on protective factors such as microbial stimulation.